1948
DOI: 10.1063/1.1697878
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Helical Antennas Radiating in the Axial Mode

Abstract: A helix is a fundamental form of antenna with many radiation modes. A recently reported mode, called an axial or beam mode, occurs for a relatively wide range of helix dimensions, in the region of 0.2 to 0.5 wave-lengths diameter and as high as 0.5 wave-lengths spacing between turns. The radiation is maximum in the direction of the helix axis and is nearly circularly polarized. This mode may persist with a given helix over a considerable frequency range. In this range the phase velocity of wave propagation alo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

1950
1950
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(16 citation statements)
references
References 5 publications
0
14
0
Order By: Relevance
“…HEN a high-gain circularly polarized antenna is required, an axial-mode helical antenna is one of the first choices [1][2][3][4]. Although this antenna has been investigated for more than five decades, for most commonly used designs it is poorly matched to the standard  50 transmission lines.…”
Section: Introductionmentioning
confidence: 99%
“…HEN a high-gain circularly polarized antenna is required, an axial-mode helical antenna is one of the first choices [1][2][3][4]. Although this antenna has been investigated for more than five decades, for most commonly used designs it is poorly matched to the standard  50 transmission lines.…”
Section: Introductionmentioning
confidence: 99%
“…We may observe three regions: the exponential decaying region away from the source, the surface wave region after the first minimum and the standing wave due to reflection of the outgoing wave at the open antenna end. The works of (Klock, 1963;Kraus, 1948Kraus, , 1949Marsh, 1950) showed that the approximate current distribution can be estimated assuming two main current waves, one with a complex valued phase constant settled in the region of normal mode (m = 0) that forms a standing wave deteriorating antenna radiation pattern, and one with real phase constant in the region of the axial mode (m = -1) that contributes to the beam radiation. The analytical procedure of a satisfying accuracy for determining the relationship between the powers of the surface waves traversing the arbitrary sized helical antenna may still be sought using a variational technique, assuming the existence of only two principal propagation modes (normal and axial), and a sinusoidal current distributions for each of them taking into account the velocities calculated for the infinite helical waveguide, as shown by (Klock, 1963).…”
Section: Helix As An Antenna Arraymentioning
confidence: 99%
“…Knowing the field components at the antenna surface, the far field in spherical coordinates (R,θ,ϑ) for each existing mode can be obtained upon by the Kirchhoff-Huygens method. The contribution to the radiated field of each space harmonic can be written in the form of the element factor and the array factor product, thus the total radiated electric field caused by the particular mode is expressed as (Cha, 1972;Kraus, 1948;Shestopalov, 1961;Vaughan & Andersen, 1985):…”
Section: Helix As An Antenna Arraymentioning
confidence: 99%
“…Cylindrical helix antenna (CHA) was invented by Kraus in 1946 [23][24][25]. It has two operation modes of circular polarization: normal mode [26] and axial mode.…”
Section: Introductionmentioning
confidence: 99%